Hybrid particle swarm optimization for first-order reliability method. (January 2017) - Wang, Gang; Ma, Zhenyue
Abstract: A reliability analysis method based on the combination of the first-order reliability method (FORM ) and hybrid particle swarm optimization (SACPSO ) is presented for the reliability optimization calculation. The new reliability method, named asSACPSO-FORM, can be utilized for those complex reliability problems with correlated non-normal variables and implicit performance functions. Three examples are performed to verify its validation, and stability reliability analysis on the complicated rock foundation of a practical gravity dam is demonstrated. The results show that the proposed method is accurate, stable, flexible and efficient for reliability analysis in engineering applications.